The Effectiveness of Leadership, Performance and Employee Involvement for Producing Competitive Advantage with a TQM Orientation: a Conceptual Framework - Abbasi, Aamna Shakeel; Aqeel, Ali Muslim Bin; Awan, Ali Naseer (Richtmann Publishing, 2012)
This paper endeavours at establishing the implication of TQM for achieving competitive advantage. The manuscriptexemplifies the role played by three major facets with relation to TQM. These three foremost areas are effective leadership,employee involvement and performance management. TQM cannot be implemented suitably without the effective leadershipprovided by the top management. The top management is in charge for the strategic goal setting for the organization and tomotivate the employees for implementing the goals. At the same time performance management is another vital area for TQMimplementation as it manages and measures the performance of each employee relative to the corporate goals of theorganization. Moreover without involving the employees in the decision making process TQM cannot be executed. Employeesare the one who transform the written strategies into practical forms so involving them in the decision making will enhance theirmotivation and interest to perform the specific task. For successful TQM execution organizations need to focus on these threeareas with respect of attaining competitive advantage in this dynamic business era and continuously evolving customer needs.